Composite fixing agent for rapidly treating pollutants and preparation method thereof

Through the synergistic effect of composite fixatives, nanosemiconductor materials, natural minerals and microbial carriers are used to solve the problems of low efficiency of water pollution control and secondary pollution risks in the existing technology, and realize the use of organic pollutants and heavy metal ions and the rapid removal of algae significantly improves the water environment.

CN119143231AInactive Publication Date: 2024-12-17GUANGZHISHUI (BEIJING) ENVIRONMENTAL PROTECTION CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411534660.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing water pollution control technology is inefficient and has poor compatibility when dealing with complex pollutants, and has the risk of secondary pollution, making it difficult to quickly remove various pollutants such as organic pollutants, heavy metal ions and algae.

Method used

Using a composite fixative composed of green nanosemiconductor materials, natural minerals, microbial carriers and functional additives, the rapid removal of organic pollutants, heavy metal ions and algae through the synergistic effects of photocatalysis, adsorption, biodegradation, etc. And ensure environmental friendliness through biocompatible materials.

Benefits of technology

It has achieved rapid and efficient removal of various pollutants, improved treatment efficiency and stability, avoided the risk of secondary pollution, significantly improved the water environment, and was especially suitable for rapid treatment of complex polluted environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143231A_ABST
    Figure CN119143231A_ABST
Patent Text Reader

Abstract

The invention discloses a composite fixing agent for rapidly treating pollutants and a preparation method thereof. The composite fixing agent is composed of a green nanometer semiconductor material, natural minerals, a microbial supporting material, a functional auxiliary agent and an environment-friendly activating agent, all the components have a synergistic effect, and efficient removal of organic pollutants, heavy metal ions, algae and main water pollutants (ammonia nitrogen, COD, total phosphorus and total nitrogen) is achieved. The preparation method comprises the following steps: pretreatment of the nano material, activation of the mineral substance, preparation of the microbial carrier, preparation of the auxiliary agent and composite synthesis. Compared with the prior art, the invention has the advantages of high treatment speed, strong adsorption capacity, wide pH application range, good biocompatibility, no secondary pollution and the like, and is suitable for emergency treatment of blue-green algae outbreak, heavy metal pollution and other sudden water pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmental pollution control, in particular to a composite fixing agent for rapidly treating pollutants and a preparation method thereof. Background Art

[0002] In existing water pollution control technologies, treatment efficiency is often limited by factors such as pollutant properties, reaction time, agent dispersibility and biocompatibility. Traditional pollution treatment agents, such as single adsorbent materials or chemical degradation agents, can have a certain removal effect on some pollutants, but their adsorption capacity is limited, the degradation rate of complex pollutant systems is slow, and their stability in the environment is poor.

[0003] Especially when dealing with sudden pollution incidents, such as blue algae outbreaks and heavy metal leaks, existing treatment technologies are difficult to achieve simultaneous removal of multiple pollutants such as organic pollutants, heavy metal ions and algae in a short period of time. In addition, some treatment agents may produce new harmful intermediates during the degradation process, posing a risk of secondary pollution and further threatening the ecological environment.

[0004] In recent years, with the rapid development of nanomaterials, some researchers have tried to apply nanomaterials to the rapid treatment of pollutants. However, the poor biocompatibility, insufficient stability and uneven distribution of nanomaterials in water bodies remain the main obstacles to their application; at the same time, a single type of material cannot effectively cover the removal needs of multiple pollutants.

[0005] Therefore, it is necessary to develop a composite fixative that combines nano-semiconductor materials, natural minerals, microbial carriers and functional additives, which can quickly and efficiently treat complex combinations of pollutants, achieve comprehensive removal of organic pollutants, heavy metal ions and algae, and have good biocompatibility and environmental friendliness. Summary of the invention

[0006] The purpose of the present invention is to provide a composite fixative for rapidly treating pollutants and a preparation method thereof, which has the advantages of rapidly degrading pollutants, being environmentally friendly and free of secondary pollution, and solves the problems of low treatment efficiency, poor compatibility and the risk of secondary pollution in the prior art.

[0007] To achieve the above object, the present invention provides the following technical solution: a composite fixative for rapidly treating pollutants, the composite fixative comprising the following components:

[0008] Green nano-semiconductor materials group: doped titanium dioxide, black phosphorus nanosheets;

[0009] Natural mineral material group: modified attapulgite, biomass carbon;

[0010] Microbial support material group: microalgae-based biofilm carriers, porous biopolymer microbeads;

[0011] Functional additive group: chitosan and its derivatives, activated carbon nanotubes;

[0012] Environmentally friendly activator group: citric acid or oxalic acid modifier, bio-based synergist.

[0013] Preferably, the ratio of each component is in the range of:

[0014] Green Nano-Semiconductor Materials Group:

[0015] Doped titanium dioxide: 50-150 parts;

[0016] Black phosphorus nanosheets: 10-30 parts;

[0017] Natural mineral material group:

[0018] Modified attapulgite: 100-300 parts;

[0019] Biomass carbon: 50-150 parts;

[0020] Microbial Support Materials Group:

[0021] Microalgae-based biofilm carrier: 20-60 parts;

[0022] Porous biopolymer microbeads: 10-40 parts;

[0023] Functional additive group:

[0024] Chitosan and its derivatives: 30-90 parts;

[0025] Activated carbon nanotubes: 10-30 parts;

[0026] Environmentally friendly activator group:

[0027] Citric acid or oxalic acid modifier: 5-15 parts;

[0028] Bio-based synergist: 10-50 parts.

[0029] Preferably, the ratio of each component is in the range of:

[0030] Green Nano-Semiconductor Materials Group:

[0031] Doped titanium dioxide: 80-120 parts;

[0032] Black phosphorus nanosheets: 15-25 parts;

[0033] Natural mineral material group:

[0034] Modified attapulgite: 150-250 parts;

[0035] Biomass carbon: 80-120 parts;

[0036] Microbial Support Materials Group:

[0037] Microalgae-based biofilm carrier: 30-50 parts;

[0038] Porous biopolymer microbeads: 20-30 parts;

[0039] Functional additive group:

[0040] Chitosan and its derivatives: 50-80 parts;

[0041] Activated carbon nanotubes: 15-25 parts;

[0042] Environmentally friendly activator group:

[0043] Citric acid or oxalic acid modifier: 8-12 parts;

[0044] Bio-based synergist: 20-40 parts.

[0045] Preferably, the surface oxygen defect concentration of the doped titanium dioxide is ≥1.0×10 18 cm -2 , light absorption range is 400-550nm, photogenerated carrier lifetime is 5-10ns, and grain size is in the range of 20-50nm;

[0046] The modified attapulgite has a cation exchange capacity of 180-200 meq / 100 g, a pore size distribution concentrated at 5-15 nm, a surface potential of -30 to -50 mV, and a pH range of 6.5-7.5;

[0047] The film thickness of the microalgae-based biofilm carrier is 1-5 μm, the pore size is 10-20 nm, the photosynthetic oxygen release rate is 6-8 mg / L / h, and the biofilm density is 0.8-1.2 g / cm 3 ;

[0048] The chelation constant of chitosan and its derivatives is ≥10 7 L / mol, molecular weight range is 100,000-500,000Da, degree of deacetylation is ≥85%, specific surface area is 50-100m 2 / g;

[0049] The molecular weight of the bio-based enhancer is 200,000-400,000Da, the gel strength is 0.8-1.0MPa, and the solubility is stable in the pH range of 6.5-7.5.

[0050] A method for preparing a composite fixing agent for rapidly treating pollutants comprises the following steps:

[0051] S1. Pretreatment of nano-semiconductor materials:

[0052] S11, dispersion of doped titanium dioxide: adding doped titanium dioxide into deionized water, stirring for 20 minutes, controlling the temperature at 25° C., to obtain dispersion A;

[0053] S12, dispersion of black phosphorus nanosheets: adding black phosphorus nanosheets into deionized water, stirring for 30 minutes, and controlling the temperature at 25° C. to obtain dispersion B;

[0054] S13, ultrasonic treatment of nanomaterials: after mixing the dispersions A and B generated by S11 and S12, adding 0.5 wt % sodium alginate, and performing ultrasonic treatment to form a uniform semiconductor material solution;

[0055] S2. Activation treatment of modified natural minerals:

[0056] S21, preparation of suspension: adding modified attapulgite and biomass carbon into deionized water at a mass ratio of 2:1, stirring at a speed of 300 rpm, and continuously stirring for 30 minutes to obtain suspension C;

[0057] S22. Improving the surface activity: Continue stirring the suspension C generated in S21 for 20 minutes to improve the surface activity of the minerals;

[0058] S23, pH adjustment: The pH of the suspension C after the activity of S22 is improved is adjusted to 7.0 using a 0.1 M sodium hydroxide solution, and the stirring time is 60 minutes to obtain an activated mineral solution;

[0059] S3. Preparation of microbial support materials:

[0060] S31, culturing a microalgae-based biofilm: mixing a microalgae culture solution with a microalgae-based biofilm carrier material in a volume ratio of 1:2, maintaining a light intensity of 2000 Lux, and culturing for 12 hours to form a preliminary biofilm solution;

[0061] S32, adding an amino acid regulator: adding an amino acid regulator to the biofilm solution obtained in S31, and stirring for 10 minutes to enhance the stability of the biofilm;

[0062] S33, mixing of microbeads: adding porous biopolymer microbeads to the solution of S32, stirring at a speed of 150 rpm for 15 minutes to obtain a microbial support solution;

[0063] S4. Preparation of functional additives:

[0064] S41, dissolving chitosan: dissolving chitosan in 0.5M acetic acid solution for 40 minutes at room temperature to obtain a basic additive solution;

[0065] S42, adding activated carbon nanotubes: adding activated carbon nanotubes to the additive solution of S41, with a mass ratio of 5% of chitosan, and adding 0.01M sodium persulfate at the same time, stirring for 30 minutes to obtain a uniform additive solution;

[0066] S5. Mixing of environmentally friendly activators:

[0067] S51, preliminary mixing of the activator: citric acid and the bio-based enhancer are mixed in deionized water, stirred for 15 minutes, and the temperature is maintained at 30° C. to form a preliminary solution;

[0068] S52, adding agar stabilizer: adding 0.5wt% agar stabilizer to the solution of S51, maintaining stirring for 20 minutes, with the temperature not lower than 45°C, to form a stable activator solution;

[0069] S6. Synthesis of composite fixative:

[0070] S61, mixing of the solutions: the semiconductor material solution of S13, the mineral solution of S23, the microbial support solution of S33, the auxiliary agent solution of S42 and the activator solution of S52 are sequentially mixed according to the ratio requirements, and stirred with step-by-step pressure increase for 40 minutes to form a composite solution;

[0071] S62, introduction of microbubbles: a microbubble generator is introduced into the composite solution of S61 to generate tiny bubbles with a diameter of 50-100 μm. The bubble generation time is continued for 20 minutes to ensure that the gas and liquid are fully mixed;

[0072] S63. Final pH adjustment: The pH of the composite solution obtained in S62 is adjusted to 6.8-7.0 to form a final liquid composite fixative, which is ready for spraying application.

[0073] Preferably, in step S13, the ultrasonic treatment adopts a variable frequency mode, and the frequency alternates between 35-45kHz; at the same time, during the addition of sodium alginate, the pH is in the range of 7.2-7.5;

[0074] In step S23, the pH is adjusted by automatic dripping, and a 0.1 M sodium hydroxide solution is dripped at a rate of 1 mL / min;

[0075] In step S31, the microalgae-based biofilm is cultured in an alternating cycle of 6 hours of light and 6 hours of darkness.

[0076] Preferably, in step S42, the dispersion of the activated carbon nanotubes adopts a three-stage stirring strategy: the initial stirring speed is 200 rpm, stirring for 10 minutes; the stirring speed is increased to 400 rpm in the middle stage, and continued for 15 minutes; and the stirring speed is finally reduced to 150 rpm, and stirred for 5 minutes;

[0077] In step S52, the dissolution temperature of agar is maintained at 50-55°C and heated in a water bath;

[0078] In step S61, the pressure-increasing stirring adopts a dynamic pressure control strategy, and the stirring is maintained for 5 minutes after each pressure increase of 0.1 MPa until it reaches 1 MPa.

[0079] Preferably, in step S62, the gas flow rate of the microbubble generator is 5-10 L / min, and the solution temperature is maintained at 20-25° C. to ensure bubble stability.

[0080] In step S63, the pH adjustment is monitored online using a high-precision pH meter, and the adjustment speed is controlled within 0.5 pH / min.

[0081] Compared with the prior art, the present invention has the following beneficial effects:

[0082] 1. By setting up a composite formula of multiple functional components, nano-semiconductor materials, natural minerals, microbial carriers and functional additives are combined to achieve the rapid removal of multiple pollutants. This composite formula shows excellent adsorption rate and degradation efficiency when dealing with organic pollutants, heavy metal ions and algae, and is suitable for rapid treatment of complex polluted environments;

[0083] 2. The use of dynamic pressurized stirring and variable frequency ultrasonic processing technology effectively improves the dispersion of materials and the uniformity of solutions, allowing each functional component to be fully integrated during the preparation process, achieving higher reaction stability and biocompatibility, and avoiding uneven distribution in water bodies;

[0084] 3. The introduction of biocompatible materials, such as microalgae-based biofilm carriers and bio-based enhancers, not only improves the environmental friendliness of the composite fixative, but also ensures that no new harmful intermediates are produced during the treatment process, thereby effectively avoiding the risk of secondary pollution;

[0085] 4. The present invention shows excellent efficiency in removing major pollutants such as ammonia nitrogen, COD, total phosphorus and total nitrogen. Through the synergistic effect of composite functional components, it achieves rapid adsorption and degradation of these eutrophication pollutants, effectively inhibits algae reproduction, prevents the occurrence of algal blooms, and significantly improves the water environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0086] Figure 1 Schematic diagram of the component structure of the composite fixing agent of the present invention;

[0087] Figure 2 Schematic diagram of the ratio range of each component of the composite fixing agent of the present invention;

[0088] Figure 3 This is a flow chart of the steps of the method for preparing the composite fixing agent of the present invention;

[0089] Figure 4 It is a schematic diagram of refined control of the preparation method of the present invention;

[0090] Figure 5 Schematic diagram of stirring and heating control of the preparation method of the present invention;

[0091] Figure 6 Schematic diagram of bubble introduction and pH monitoring of the present invention. DETAILED DESCRIPTION

[0092] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0093] See also Figures 1 to 6 The present invention relates to a composite fixative for rapidly treating pollutants. The innovation of the composite fixative is the composite use of multiple functional components to improve the treatment efficiency and stability of pollutants. In the specific implementation process, by rationally selecting and proportioning different functional materials, efficient removal of multiple pollutants and environmental friendliness are achieved.

[0094] Composition and ratio of composite fixative

[0095] The composite fixative is composed of the following five components, each of which plays a synergistic role in the treatment of pollutants in different aspects:

[0096] Green Nano-Semiconductor Materials Group:

[0097] It contains doped titanium dioxide and black phosphorus nanosheets. Doped titanium dioxide is doped with metal or non-metal elements to enhance its photocatalytic activity and improve the degradation efficiency of organic pollutants. Black phosphorus nanosheets have high adsorption capacity and can capture heavy metal ions and some organic matter in water. The proportion of this component ranges from 50-150 parts of doped titanium dioxide to 10-30 parts of black phosphorus nanosheets.

[0098] In practical applications, this material group can excite electron-hole pairs under light conditions, thereby oxidizing and degrading pollutants. The application of doping technology allows the photocatalytic properties of titanium dioxide to work under visible light, expanding its scope of use.

[0099] Natural mineral material group:

[0100] It includes modified attapulgite and biomass carbon. Modified attapulgite has excellent adsorption performance and ion exchange capacity, and its adsorption capacity and stability for heavy metal ions are further improved through chemical modification. Biomass carbon is a porous structure material obtained through high-temperature carbonization process, which has a large specific surface area and good adsorption performance. The ratio range is 100-300 parts of modified attapulgite and 50-150 parts of biomass carbon.

[0101] The main function of this component is to remove heavy metal ions and organic pollutants from water bodies through physical adsorption and chemical chelation. The synergistic effect of modified attapulgite and biomass carbon can significantly increase the pollutant loading capacity of the composite fixative while ensuring the stability of the treatment process.

[0102] Microbial Support Materials Group:

[0103] It includes microalgae-based biofilm carriers and porous biopolymer microbeads. The microalgae-based biofilm carriers can not only have good contact with pollutants in the water, but also provide physical support and nutritional basis for the growth of microorganisms. The porous biopolymer microbeads increase the surface area and durability of the biofilm by providing a porous structure. The ratio range is 20-60 parts of microalgae-based biofilm carriers and 10-40 parts of porous biopolymer microbeads.

[0104] This component plays a role in biocompatibility in the process of pollutant treatment, allowing microorganisms to grow on the carrier and decompose organic pollutants, which is particularly suitable for the removal of biological pollutants. At the same time, the microalgae-based biofilm can also absorb nitrogen and phosphorus in the water to further purify the water quality.

[0105] Functional additive group: contains chitosan and its derivatives and activated carbon nanotubes. Chitosan and its derivatives have good chelating ability and strong adsorption capacity for metal ions, while also improving the overall adhesion of the composite fixative. Activated carbon nanotubes enhance the adsorption and fixation capacity of the material through a porous structure. The ratio range is 30-90 parts of chitosan and its derivatives and 10-30 parts of activated carbon nanotubes.

[0106] The addition of this component not only improves the mechanical strength of the composite fixative, but also enhances its physical fixation ability and chemical chelation effect on pollutants, thereby improving the durability and efficiency of the material.

[0107] Environmentally friendly activator group: contains citric acid or oxalic acid modifier and bio-based synergist. Citric acid or oxalic acid modifier can stabilize pollutants through complex reaction, making it difficult to release into the water. Bio-based synergist plays a role in improving the reactivity of materials. The ratio range is 5-15 parts of citric acid or oxalic acid modifier and 10-50 parts of bio-based synergist.

[0108] The design of this component is intended to ensure that the composite fixative has no risk of secondary contamination during use, while improving the fixation and degradation capabilities of pollutants.

[0109] In actual use, the composite fixative can remove pollutants simultaneously by fully contacting the polluted water body and utilizing the different functions of each component. The green nano-semiconductor material degrades organic pollutants in the photocatalytic reaction, the natural mineral material removes heavy metal pollutants through adsorption and ion exchange, and the microbial support material further decomposes and adsorbs organic pollutants, while promoting the ecological balance in the water body.

[0110] The entire treatment process is not only fast, but also easy to operate and has efficient pollutant degradation and adsorption capabilities, solving the problem of low efficiency of traditional treatment agents in complex pollutant systems.

[0111] By optimizing the selection and ratio of components, the present invention not only solves the stability and treatment range limitations of traditional treatment agents, but also achieves efficient and environmentally friendly simultaneous treatment of multiple pollutants. This composite fixative can significantly reduce the concentration of pollutants in water within 48 hours and maintain stable treatment effects during long-term use.

[0112] In terms of technical characteristics, the composite fixing agent of the present invention improves its performance in the process of pollutant treatment by optimizing the physical and chemical properties of various key functional materials.

[0113] The surface oxygen defect concentration is ≥1.0×10 18 cm -2 :The concentration of oxygen defects on the surface of doped titanium dioxide is high, which can enhance the photocatalytic activity of the material. Oxygen defects help capture photogenerated electrons and prevent the rapid recombination of electron-hole pairs, thereby improving the degradation efficiency of organic pollutants.

[0114] The light absorption range is 400-550nm: This absorption range covers the visible light band, which means that the material can be excited and undergo photocatalytic reactions under natural light or artificial light, thereby expanding the application conditions.

[0115] The lifetime of photogenerated carriers is 5-10ns: the longer the lifetime of photogenerated carriers, the more time they have to participate in the photocatalytic reaction, which is beneficial to improving the degradation effect of pollutants.

[0116] The grain size is in the range of 20-50nm: This nanoscale grain size provides a large specific surface area, thereby increasing the contact area with pollutants, helping to improve the degradation speed and efficiency.

[0117] The cation exchange capacity is 180-200meq / 100g: High cation exchange capacity means that the material has a strong heavy metal adsorption capacity and can effectively remove heavy metal pollutants in water through the ion exchange mechanism.

[0118] The pore size distribution is concentrated in 5-15nm: This pore size distribution can adapt to pollutants of different molecular sizes, and can capture organic matter through physical adsorption and remove heavy metal ions through ion exchange.

[0119] The surface potential is -30 to -50 mV: The negative range of the surface potential is large, indicating that the material has a high dispersion stability in the water body, which is conducive to maintaining a suspended state in the water body, thereby improving the treatment efficiency.

[0120] The pH range is 6.5-7.5: This pH range has strong adaptability, which allows the modified attapulgite to exist stably under the pH conditions of natural water bodies and will not lose its activity due to changes in acidity and alkalinity.

[0121] The film thickness is 1-5μm: The thinner film thickness enables the microalgae-based biofilm to better adhere to the carrier surface, while improving its photosynthesis efficiency and pollutant adsorption capacity.

[0122] Pore ​​size is 10-20nm: This degree of pore size can support the growth of microorganisms in biofilms while effectively adsorbing organic pollutants and nutrients in water.

[0123] The photosynthetic oxygen release rate is 6-8 mg / L / h: A higher oxygen release rate enhances the dissolved oxygen level in the water, which is beneficial to further promote the biodegradation of organic matter.

[0124] The biofilm density is 0.8-1.2 g / cm 3 :This density range helps to improve the stability and durability of the biofilm, ensuring its long-term existence and continued function in the water body.

[0125] The chelation constant is ≥10 7 L / mol: Chitosan has a high chelating ability and can effectively fix heavy metal ions in water, preventing heavy metals from being released back into the water during the treatment process.

[0126] Molecular weight range is 100,000-500,000Da: High molecular weight chitosan helps to improve the adhesion and mechanical strength of the solution, thereby improving the overall performance of the composite fixative.

[0127] Deacetylation degree is ≥85%: Chitosan with high deacetylation degree has stronger biodegradability and chelating properties, and can form stable chelates with heavy metal ions and organic pollutants.

[0128] Specific surface area is 50-100m 2 / g: The larger specific surface area provides more active sites for the adsorption of pollutants and improves the treatment effect.

[0129] Molecular weight is 200,000-400,000Da: The high molecular weight enables the bio-based enhancer to provide a stable enhancement effect and work synergistically with other components to improve the removal efficiency of pollutants.

[0130] The gel strength is 0.8-1.0MPa: The higher gel strength gives the material good stability and mechanical properties in water, making it difficult to decompose or dissolve, ensuring its continued function.

[0131] Solubility is stable in the pH range of 6.5-7.5: This stability allows the bio-based enhancer to maintain chemical stability in the natural pH environment of the water body and avoid being affected by changes in the acidity and alkalinity of the water body.

[0132] During the preparation process, the composite fixative of the present invention optimizes the dispersion, activation and synergy of each key functional material, thereby improving the treatment effect of various pollutants and the stability and durability of the material. Specifically, the following steps are included:

[0133] S1. Pretreatment of Nano-semiconductor Materials

[0134] S11. Dispersion of doped titanium dioxide: Add doped titanium dioxide to deionized water and stir with a high shear mixer for 20 minutes at 25°C. The purpose of high shear stirring is to promote uniform dispersion of titanium dioxide particles and increase the specific surface area of ​​the material, thereby increasing its photocatalytic activity and the probability of contact with pollutants. This process breaks the agglomeration state of the particles to ensure that the effective active sites of titanium dioxide are maximized in the subsequent treatment process.

[0135] S12. Dispersion of black phosphorus nanosheets: Add black phosphorus nanosheets to deionized water, and use a high shear mixer for 30 minutes at a temperature of 25°C. Due to the easy oxidation of black phosphorus, the operation needs to be carried out in a closed environment. The unique two-dimensional structure and high adsorption of black phosphorus determine its ability to capture organic pollutants, and full dispersion helps to increase its contact area with pollutants.

[0136] S13, ultrasonic treatment of nanomaterials: After mixing the dispersions A and B generated by S11 and S12, add 0.5wt% sodium alginate solution for ultrasonic treatment. The ultrasonic frequency is set to 40kHz and the ultrasonic time is 15 minutes. Ultrasonic treatment further disperses the nanomaterials into monomer particles through the acoustic cavitation effect, and forms a stable charge layer on the surface of the particles to prevent the material from agglomerating, while improving the suspension and stability of the material. This uniform dispersion state makes the active sites of the photocatalytic reaction evenly distributed, improving the degradation efficiency of pollutants.

[0137] S2. Activation treatment of modified natural minerals

[0138] S21, preparation of suspension: modified attapulgite and biomass carbon are added to deionized water at a mass ratio of 2:1, and stirred using a stirrer with a scraper, with the stirring speed set at 300 rpm for 30 minutes. This process ensures that the attapulgite and biomass carbon are evenly dispersed in water, thereby ensuring that they can fully exert their adsorption and ion exchange capabilities in subsequent steps.

[0139] S22. Improvement of surface activity: Continue stirring in the suspension C generated in S21 for 20 minutes. The purpose of this step is to further open the layered structure of attapulgite and the pores of biomass carbon through mechanical stirring. After the surface activity of the material is improved, its adsorption capacity for heavy metal ions and organic pollutants is significantly enhanced.

[0140] S23, pH adjustment: The pH of the S22 suspension was adjusted to 7.0 by slowly adding 0.1M sodium hydroxide solution, and the stirring time was 60 minutes. The pH was adjusted to neutral to activate the ion exchange capacity of the material, so that it can maintain a strong metal ion adsorption efficiency during the water treatment process and maintain the stability of the material during the treatment process.

[0141] S3. Preparation of microbial support materials

[0142] S31. Cultivation of microalgae-based biofilm: Mix the microalgae culture solution and the microalgae-based biofilm carrier material in a volume ratio of 1:2 and culture for 12 hours under a light intensity of 2000 Lux. This process simulates the photosynthetic environment in natural water bodies and enhances the photosynthetic activity of microalgae and the efficiency of biofilm formation by adjusting the light cycle. The density and thickness of the biofilm gradually increase during the cultivation process, laying the foundation for the subsequent degradation and adsorption of pollutants.

[0143] S32. Adding amino acid regulator: Add amino acid regulator to the preliminary biofilm solution generated in S31 and stir for 10 minutes. The amino acid regulator enhances the biodegradation ability of the biofilm to organic pollutants by improving the nutrient level and stability of the biofilm.

[0144] S33, mixing of microbeads: adding porous biopolymer microbeads to the biofilm solution of S32, and setting the stirring speed to 150 rpm for 15 minutes. The structure of the porous microbeads can increase the attachment area and durability of the biofilm, making it more effective in maintaining activity during the pollutant treatment process.

[0145] S4. Preparation of functional additives

[0146] S41. Dissolution of chitosan: Dissolve chitosan in 0.5M acetic acid solution, stir with a stirrer for 40 minutes at room temperature. Chitosan is partially hydrolyzed during the dissolution process to form a solution with high chelating ability, which provides chelating and stabilizing functions for the preparation of the composite fixative.

[0147] S42, addition of activated carbon nanotubes: Add activated carbon nanotubes to the chitosan solution of S41, and add 0.01M sodium persulfate at the same time, and stir for 30 minutes. The addition of activated carbon nanotubes helps to improve the adsorption of the solution, while sodium persulfate further improves the chelation and fixation ability of chitosan through oxidation.

[0148] S5. Mixing of environmentally friendly activators

[0149] S51. Preliminary mixing of activators: Mix citric acid or oxalic acid with the bio-based enhancer in deionized water, stirring for 15 minutes, and controlling the temperature at 30°C. Citric acid or oxalic acid, as a complexing agent, can stabilize the pollutants and make them less likely to dissolve or release back into the water.

[0150] S52, adding agar stabilizer: add 0.5wt% agar stabilizer to the solution of S51, and continue stirring for 20 minutes, with the temperature not lower than 45° C. The addition of agar makes the activator solution have appropriate viscosity and stability, ensuring that it does not stratify or precipitate during the mixing process.

[0151] S6. Synthesis of composite fixative

[0152] S61, mixing of solutions: the semiconductor material solution of S13, the mineral solution of S23, the microbial support solution of S33, the additive solution of S42 and the activator solution of S52 are mixed in sequence. The initial pressure is set to 0.5MPa and gradually increased to 1MPa, and the stirring time is 40 minutes. The pressure-boosting stirring ensures that the components are evenly dispersed and improves the stability and durability of the composite solution.

[0153] S62, introduction of microbubbles: introduce a microbubble generator into the composite solution of S61, with a bubble diameter of 50-100μm, and continue to generate bubbles for 20 minutes. The introduction of microbubbles increases the contact opportunity between pollutants and composite fixatives through the expansion of the gas-liquid interface, thereby improving the adsorption and degradation efficiency.

[0154] S63. Final pH adjustment: Adjust the pH of the composite solution of S62 to 6.8-7.0. By controlling the pH, the stability and efficiency of the composite fixative in the application environment are ensured, which is convenient for subsequent spraying applications.

[0155] The composite fixative preparation method of the present invention achieves efficient removal of various pollutants such as organic pollutants, heavy metal ions and algae by finely controlling the dispersion, activation and synergistic effect of the materials. The optimization treatment of each step not only ensures the uniform distribution and stability of the materials, but also enhances the adsorption and degradation capacity of pollutants through specific physical and chemical conditions. The composite fixative finally obtained has significant advantages in environmental friendliness, biocompatibility and treatment efficiency, and provides an ideal solution for the rapid treatment of complex polluted water bodies.

[0156] Among them, in step S13, the ultrasonic treatment adopts a variable frequency mode, and the frequency alternates between 35-45kHz: variable frequency ultrasonic treatment is to enhance the dispersion effect of nanomaterials by constantly changing the frequency. At a fixed frequency, ultrasound may form standing waves in the liquid, resulting in uneven energy in local areas, while variable frequency treatment can avoid the generation of standing waves and ensure the uniform distribution of energy in the solution, thereby making the dispersion of titanium dioxide and black phosphorus nanosheets more thorough.

[0157] Adding sodium alginate within the pH range of 7.2-7.5 helps to form a stable colloidal solution. This pH range can maintain the negative charge state of sodium alginate, allowing it to form a stable charge layer in the solution, prevent the agglomeration of nanoparticles, and ensure the uniformity and high reactivity of the material.

[0158] In step S23, the pH is adjusted by an automatic dripping device, and 0.1M sodium hydroxide solution is dripped at a rate of 1mL / min: the application of the automatic dripping device is to ensure the accuracy and stability of the pH adjustment process. The dripping speed of 1mL / min can avoid rapid fluctuations in the pH of the solution and prevent the material from experiencing performance degradation or inactivation due to drastic pH changes. This precise pH control not only enhances the ion exchange capacity of attapulgite, but also helps to improve the stability of the composite fixative when treating heavy metals.

[0159] In step S31, the cultivation of microalgae-based biofilm adopts an alternating cycle of 6 hours of light and 6 hours of darkness: this alternating light and dark cycle simulates the day and night light conditions in the natural environment, which is conducive to the growth of microalgae and the formation of biofilm. During the daytime light period, microalgae produce oxygen and absorb pollutants through photosynthesis; at night, they further degrade organic pollutants through metabolism. This alternating light cycle can improve the activity and durability of the biofilm, enhance the biocompatibility and multi-pollutant treatment ability of the composite fixative.

[0160] In step S42, a three-stage stirring strategy was used for the dispersion of activated carbon nanotubes: the initial stirring speed was 200 rpm for 10 minutes to ensure the initial dispersion of the nanotubes; the speed was increased to 400 rpm for 15 minutes in the middle stage to enhance the mixing uniformity of the nanotubes and the chitosan solution; the speed was reduced to 150 rpm for 5 minutes in the final stage to prevent the dispersed nanotubes from structural damage due to high shear.

[0161] The purpose of this dispersion strategy is to enable the activated carbon nanotubes to be fully dispersed in the chitosan solution without agglomeration by gradually increasing and decreasing the stirring speed, while maintaining the fluidity and stability of the solution, thereby improving the adsorption performance of the composite immobilizer.

[0162] In step S52, the dissolution temperature of agar is maintained at 50-55°C and heated in a water bath: within this temperature range, agar can be dissolved more evenly to form a stable colloidal solution. Water bath heating can prevent gelation caused by local overheating while maintaining the viscosity and uniformity of the solution. This stable activator solution helps the continuous release of the composite fixative in the water body and improves the fixation and degradation efficiency of pollutants.

[0163] In step S61, the pressure-boosting stirring adopts a dynamic pressure control strategy: stirring is maintained for 5 minutes after each pressure increase of 0.1MPa until it reaches 1MPa. Dynamic pressure-boosting stirring gradually increases the pressure to mix the components in the solution more evenly, avoiding the problem of uneven bubble generation caused by rapid pressure increase. By gradually increasing the pressure and maintaining stirring, the structural stability and mixing uniformity of the composite fixative are ensured, and the reaction effect of the composite material during the treatment process is improved.

[0164] In step S62, the gas flow rate of the microbubble generator is set to 5-10L / min, and the solution temperature is maintained at 20-25°C: the gas flow rate can generate stable microbubbles (with a diameter of 50-100μm) in the composite solution, and ensure the stability of the bubbles in the solution by maintaining the appropriate temperature of the solution. The stability of the bubbles is crucial to the expansion of the gas-liquid interface, which helps to increase the contact probability between the pollutant and the composite fixative, thereby improving the adsorption and degradation efficiency.

[0165] In step S63, the pH adjustment is monitored online using a high-precision pH meter, and the adjustment speed is controlled within 0.5 pH / min: through real-time monitoring by a high-precision pH meter, it is possible to ensure that the composite solution remains within the target range of 6.8-7.0 during the adjustment process. Controlling the adjustment speed can prevent drastic fluctuations in pH and ensure the stability and processing efficiency of the composite fixative after adjustment.

[0166] In order to further verify the practical application effect and technical advantages of the composite fixative of the present invention, multiple examples under different scenarios were designed, and specific comparative experiments were conducted to demonstrate in detail its superior performance in the treatment of different pollutants. The following are the implementation effects of the present invention in two typical application scenarios: emergency treatment of cyanobacteria outbreaks and treatment of heavy metal polluted water bodies;

[0167] Example 1: Emergency treatment of blue algae outbreak

[0168] Blue algae outbreaks are a common water pollution problem, usually caused by excessive nutrients in the water, such as excessive concentrations of nitrogen and phosphorus. Blue algae outbreaks not only reduce the dissolved oxygen content of the water, but also release harmful substances, affecting the water quality and ecological environment. Traditional blue algae treatment methods mostly rely on chemical agents, which have low treatment efficiency, short-term effects and the risk of secondary pollution. The composite fixative of the present invention aims to achieve rapid and efficient treatment of blue algae pollution through synergistic effects, especially in emergency scenarios. It is suitable for emergency treatment of blue algae outbreaks in large water bodies such as drinking water sources, landscape water bodies and agricultural water.

[0169] This embodiment achieves rapid removal of cyanobacteria through the photocatalytic properties of nano-semiconductor materials and the biodegradability of microalgae-based biofilms. During the experiment, the composite fixative was added to the cyanobacteria-contaminated water body, and its cyanobacteria removal effect within 48 hours was monitored and compared with the traditional cyanobacteria treatment technology.

[0170] Experimental results:

[0171]

[0172] The experimental results show that the use of the composite fixative of the present invention can significantly reduce the concentration of cyanobacteria within 48 hours and significantly increase the dissolved oxygen content of the water body, while avoiding secondary pollution, and is suitable for long-term application in emergency treatment of cyanobacteria.

[0173] Example 2: Treatment of heavy metal polluted water

[0174] Heavy metal pollution is a common pollution problem in industrial wastewater and mine drainage. Heavy metal ions such as lead, cadmium, and mercury pose a serious threat to water bodies and the ecological environment. Traditional adsorption materials are usually unstable and prone to secondary pollution. The composite fixative of the present invention achieves efficient adsorption and stable fixation of heavy metal ions through a multifunctional design, ensuring that there is no risk of secondary pollution in the treated water.

[0175] It is suitable for the efficient treatment of heavy metal pollution sources such as industrial wastewater, mine drainage and soil leachate.

[0176] The composite fixative of the present invention is added to a heavy metal polluted water body, and its adsorption effect on various heavy metals is observed through a 24-hour experimental period, and compared with traditional adsorption materials.

[0177] Experimental results:

[0178]

[0179] Experimental results show that the composite fixative of the present invention can achieve efficient adsorption and fixation of heavy metal ions in a short time, while maintaining stability in a wide pH range, with no risk of heavy metal release, and is suitable for heavy metal treatment needs in a variety of water environments.

[0180] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A composite fixative for rapidly treating pollutants, characterized in that: The composite fixative is composed of the following components: Green nano-semiconductor materials group: doped titanium dioxide, black phosphorus nanosheets; Natural mineral material group: modified attapulgite, biomass carbon; Microbial support material group: microalgae-based biofilm carriers, porous biopolymer microbeads; Functional additive group: chitosan and its derivatives, activated carbon nanotubes; Environmentally friendly activator group: citric acid or oxalic acid modifier, bio-based synergist.

2. A composite fixing agent for rapid treatment of pollutants according to claim 1, characterized in that: The ratio range of each component is: Green Nano-Semiconductor Materials Group: Doped titanium dioxide: 50-150 parts; Black phosphorus nanosheets: 10-30 parts; Natural mineral material group: Modified attapulgite: 100-300 parts; Biomass carbon: 50-150 parts; Microbial Support Materials Group: Microalgae-based biofilm carrier: 20-60 parts; Porous biopolymer microbeads: 10-40 parts; Functional additive group: Chitosan and its derivatives: 30-90 parts; Activated carbon nanotubes: 10-30 parts; Environmentally friendly activator group: Citric acid or oxalic acid modifier: 5-15 parts; Bio-based synergist: 10-50 parts.

3. A composite fixing agent for rapid treatment of pollutants according to claim 2, characterized in that: The ratio range of each component is: Green Nano-Semiconductor Materials Group: Doped titanium dioxide: 80-120 parts; Black phosphorus nanosheets: 15-25 parts; Natural mineral material group: Modified attapulgite: 150-250 parts; Biomass carbon: 80-120 parts; Microbial Support Materials Group: Microalgae-based biofilm carrier: 30-50 parts; Porous biopolymer microbeads: 20-30 parts; Functional additive group: Chitosan and its derivatives: 50-80 parts; Activated carbon nanotubes: 15-25 parts; Environmentally friendly activator group: Citric acid or oxalic acid modifier: 8-12 parts; Bio-based synergist: 20-40 parts.

4. The composite fixing agent for rapid treatment of pollutants according to claim 1, characterized in that: The surface oxygen defect concentration of the doped titanium dioxide is ≥1.0×10 18 cm -2 , light absorption range is 400-550nm, photogenerated carrier lifetime is 5-10ns, and grain size is in the range of 20-50nm; The modified attapulgite has a cation exchange capacity of 180-200 meq / 100 g, a pore size distribution concentrated at 5-15 nm, a surface potential of -30 to -50 mV, and a pH range of 6.5-7.5; The film thickness of the microalgae-based biofilm carrier is 1-5 μm, the pore size is 10-20 nm, the photosynthetic oxygen release rate is 6-8 mg / L / h, and the biofilm density is 0.8-1.2 g / cm 3 ; The chelation constant of chitosan and its derivatives is ≥10 7 L / mol, molecular weight range is 100,000-500,000Da, degree of deacetylation is ≥85%, specific surface area is 50-100m 2 / g; The molecular weight of the bio-based enhancer is 200,000-400,000 Da, the gel strength is 0.8-1.0 MPa, and the solubility is stable in the pH range of 6.5-7.

5.

5. A method for preparing a composite fixing agent for rapidly treating pollutants, applied to a composite fixing agent for rapidly treating pollutants as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Pretreatment of nano-semiconductor materials: S11, dispersion of doped titanium dioxide: adding doped titanium dioxide into deionized water, stirring for 20 minutes, controlling the temperature at 25° C., to obtain dispersion A; S12, dispersion of black phosphorus nanosheets: adding black phosphorus nanosheets into deionized water, stirring for 30 minutes, and controlling the temperature at 25° C. to obtain dispersion B; S13, ultrasonic treatment of nanomaterials: after mixing the dispersions A and B generated by S11 and S12, adding 0.5 wt % sodium alginate, and performing ultrasonic treatment to form a uniform semiconductor material solution; S2. Activation treatment of modified natural minerals: S21, preparation of suspension: adding modified attapulgite and biomass carbon into deionized water at a mass ratio of 2:1, stirring at a speed of 300 rpm, and continuously stirring for 30 minutes to obtain suspension C; S22. Improving the surface activity: Continue stirring the suspension C generated in S21 for 20 minutes to improve the surface activity of the minerals; S23, pH adjustment: The pH of the suspension C after the activity of S22 is improved is adjusted to 7.0 using a 0.1 M sodium hydroxide solution, and the stirring time is 60 minutes to obtain an activated mineral solution; S3. Preparation of microbial support materials: S31, culturing a microalgae-based biofilm: mixing a microalgae culture solution with a microalgae-based biofilm carrier material in a volume ratio of 1:2, maintaining a light intensity of 2000 Lux, and culturing for 12 hours to form a preliminary biofilm solution; S32, adding an amino acid regulator: adding an amino acid regulator to the biofilm solution obtained in S31, and stirring for 10 minutes to enhance the stability of the biofilm; S33, mixing of microbeads: adding porous biopolymer microbeads to the solution of S32, stirring at a speed of 150 rpm for 15 minutes to obtain a microbial support solution; S4. Preparation of functional additives: S41, dissolving chitosan: dissolving chitosan in 0.5M acetic acid solution for 40 minutes at room temperature to obtain a basic additive solution; S42, adding activated carbon nanotubes: adding activated carbon nanotubes to the additive solution of S41, with a mass ratio of 5% of chitosan, and adding 0.01M sodium persulfate at the same time, stirring for 30 minutes to obtain a uniform additive solution; S5. Mixing of environmentally friendly activators: S51, preliminary mixing of the activator: citric acid and the bio-based enhancer are mixed in deionized water, stirred for 15 minutes, and the temperature is maintained at 30° C. to form a preliminary solution; S52, adding agar stabilizer: adding 0.5wt% agar stabilizer to the solution of S51, maintaining stirring for 20 minutes, with the temperature not lower than 45°C, to form a stable activator solution; S6. Synthesis of composite fixative: S61, mixing of the solutions: the semiconductor material solution of S13, the mineral solution of S23, the microbial support solution of S33, the auxiliary agent solution of S42 and the activator solution of S52 are sequentially mixed according to the ratio requirements, and stirred with step-by-step pressure increase for 40 minutes to form a composite solution; S62, introduction of microbubbles: a microbubble generator is introduced into the composite solution of S61 to generate tiny bubbles with a diameter of 50-100 μm. The bubble generation time is continued for 20 minutes to ensure that the gas and liquid are fully mixed; S63. Final pH adjustment: The pH of the composite solution obtained in S62 is adjusted to 6.8-7.0 to form a final liquid composite fixative, which is ready for spraying application.

6. The method for preparing a composite fixing agent for rapid treatment of pollutants according to claim 5, characterized in that: In step S13, the ultrasonic treatment adopts a variable frequency mode, and the frequency alternates between 35-45kHz; at the same time, during the addition of sodium alginate, the pH is in the range of 7.2-7.5; In step S23, the pH is adjusted by automatic dripping, and a 0.1 M sodium hydroxide solution is dripped at a rate of 1 mL / min; In step S31, the microalgae-based biofilm is cultured in an alternating cycle of 6 hours of light and 6 hours of darkness.

7. The method for preparing a composite fixing agent for rapid treatment of pollutants according to claim 5, characterized in that: In step S42, the activated carbon nanotubes were dispersed using a three-stage stirring strategy: the initial stirring speed was 200 rpm for 10 minutes; the stirring speed was increased to 400 rpm for 15 minutes in the middle stage; and the stirring speed was finally reduced to 150 rpm for 5 minutes. In step S52, the dissolution temperature of agar is maintained at 50-55°C and heated in a water bath; In step S61, the pressure-increasing stirring adopts a dynamic pressure control strategy, and the stirring is maintained for 5 minutes after each pressure increase of 0.1 MPa until it reaches 1 MPa.

8. The method for preparing a composite fixing agent for rapid treatment of pollutants according to claim 5, characterized in that: In step S62, the gas flow rate of the microbubble generator is 5-10 L / min, and the solution temperature is maintained at 20-25° C. to ensure bubble stability; In step S63, the pH adjustment is monitored online using a high-precision pH meter, and the adjustment speed is controlled within 0.5 pH / min.

Citation Information

Cited By

  • Biomass nano-porous water treatment agent and preparation method thereof

    CN120571555A